Use of laser-induced break spectroscopy for the determination of major and trace elements in Zanthoxylum armatum - Shabnam Shahida (13131808) (2020)
Zanthoxylum armatum (ZA) is a medicinal plant (MP) that is widely distributed in hilly and moist areas and has a different medical effect on human curative functions. Laser-induced breakdown spectroscopy (LIBS) was employed as a simple, easy, and accurate method to analyze the elemental profile of Zanthoxylum armatum (ZA) (timur). Various elements present in different parts of ZA were identified including sodium, magnesium, calcium, potassium, titanium, iron, barium, aluminum, lithium, and silicon. The proposed method accuracy was found to be comparable with high technical complicated lab equipment The concentrations of these elements were determined and were found to be below the toxic level. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-020-00095-0